RELATIONSHIP BETWEEN COMPETENCY OF SCHOOL ADMINISTRATORS AND EFFECTIVENESS OF PRIVATE SCHOOLS IN PATHUMTHANI PROVINCE - Rumakhom, Vassiga (Journal of MCU Nakhondhat, 2022)
The purposes of this research were to 1) study competency of school administrators 2) study effectiveness of private schools in Pathumthani province and 3) study relationship between competency of school administrators and effectiveness of private schools in Pathumthani province, based on the quantitative research. The population consisted of 2,325 teachers of private schools in Pathumthani province and the sample was 341 teachers. Determine the size of the sample by using Taro Yamane’s formula. The tool used in this research was the 5 scale rating questionnaire, concerning school administrator’s competency, based on the Teachers Council of Thailland and effectiveness of private schools in Pathumthani province, based on Kaplan and Norton’s Balanced Scorcard. IOC was between 0.67-1.00 and the reliability values were 0.98. Statistical analysis methods used to analyze the data in this research were frequency distribution, percentage, mean, standard deviation and Pearson’s correlation coefficient. The results have shown as followed, 1) Competency of school administrators in overall was at a high level. When considered as individual aspects found that every aspect was at a high level, excluding student affair and activity aspect with its mean at a highest level. 2) Effectiveness of private schools in Pathumthani province in overall was at a high level. When considered as individual aspects found that every aspect was at a high level. 3) There was a positive, very high level relationship between competency of school administrators and effectiveness of private schools in Pathumthani province.